Comparison of school training features in Ukraine, India and Israel, affecting the adaptation to the system of higher medical education in Ukraine - Pototskaya, O. Yu.; Shevchenko, K. M. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. In conditions of reduce the amount of local applicants, the attraction of citizens of other countries for studying in Ukraine becomes particularly relevant. To ensure this the most effective adaptation of foreign applicants to the system of national higher education should be provided. Since different countries have their own features of school education, and school education differs from university education, it is expediently to highlight the most critical inconsistencies of these systems and to focus attention of first-year students on them. Objective. The purpose of the article was to compare the features of education in schools in Ukraine, India and Israel, which affect adaptation to the system of higher medical education in Ukraine. Methods. To solve the task, the students of the 1st, 2nd year of the Dnepropetrovsk Medical Academy of the Ministry of Health of Ukraine were questioned. The survey involved 98 students from Israel, 100 from Ukraine, 100 from India. Results. The results of the data analysis of a survey have revealed that Ukrainian students are most adapted to study in higher medical institutions of our country, although they face a number of difficulties that related to the change in the assessment, increasing importance of self-education and the need for regular preparation for each lesson. Students from Israel are faced with the most inconsistencies between the systems of their school education and Ukrainian higher education. First of all, they are studying in a non-native language and the language of their education in the university differs from the language in the school. In addition, they are less inured to self-work (in comparison with the other two groups of comparison) and demonstrate greater dependence on the teacher in the studying process. Also, students of this category may underestimate the value of marks that they receive in practical lessons and the regular preparation of a homework. An additional stress for these students is the need to reply orally, as well as the fact of publicity of the achievement scores. For students from India, one of the most significant moments in adaptation is the need to reply orally and to be assessed on each class. They are also less adapted to self-work as compared with Ukrainian students. Сonclusions. Obtained results evidence the necessity to work differentially with foreign students taking into account the peculiarities of school education in their countries.